2004
DOI: 10.1074/jbc.m311184200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitogen-activated Protein Kinases in 4-Hydroxy-2-nonenal-induced Actin Remodeling and Barrier Function in Endothelial Cells

Abstract: In vivo and in vitro studies indicate that 4-hydroxy-2-nonenal (4-HNE), generated by cellular lipid peroxidation or after oxidative stress, affects endothelial permeability and vascular tone. However, the mechanism(s) of 4-HNE-induced endothelial barrier function is not well defined. Here we provide evidence for the first time on the involvement of mitogen-activated protein kinases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 60 publications
(74 reference statements)
4
108
1
Order By: Relevance
“…12), confirming a major role for NADPH oxidase. Although signaling pathways whereby hyperoxia regulates endothelial NADPH oxidase have not been completely defined, involvement of MAPKs in NADPH oxidase activation and ROS production has been reported (10,44). Previous studies in human vascular and rat thoracic aortic VSMCs demonstrated that angiotensin II-dependent stimulation of NADPH oxidase is regulated in part by c-Src (18).…”
Section: Discussionmentioning
confidence: 99%
“…12), confirming a major role for NADPH oxidase. Although signaling pathways whereby hyperoxia regulates endothelial NADPH oxidase have not been completely defined, involvement of MAPKs in NADPH oxidase activation and ROS production has been reported (10,44). Previous studies in human vascular and rat thoracic aortic VSMCs demonstrated that angiotensin II-dependent stimulation of NADPH oxidase is regulated in part by c-Src (18).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that the mechanism of HO-1 induction by HNE in pulmonary epithelial cells is different from other systems. As the lung is the "first line of defense," it is not surprising that pulmonary epithelial cells may have evolved mechanisms to rapidly respond to cellular insults.It is well established in the literature that HNE activates some, or even all, of the MAPK in other cell systems [38,[59][60][61][62]. We hypothesized that HNE-mediated activation of MAPK signaling pathways culminated in phosphorylation and/or nuclear translocation of transcription factors critical to the induction of HO-1 mRNA synthesis and was thus the mechanism for increased HO-1 protein and activity.…”
mentioning
confidence: 96%
“…Free radical-mediated lipid peroxidation and its reactive byproducts, like HNE are known to cause cellular structural perturbations and various redox-related degenerative processes, including vascular dysfunction [12,20,36]. To assess the HNE-induced oxidative stress in vascular endothelial cells, we analyzed ROS production using confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…These reactive aldehydes are known to cause redox disturbances and various degenerative processes, including the vascular dysfunction associated with aging [12,20,37]. It seems logical that HNE and HHE are the subjects of recent intensified studies investigating their roles in the modulation of cell signaling pathways and the induction of apoptosis [2,15,36]. HNE as a potent cytotoxic agent is a byproduct of n-6 fatty acid peroxidation [12,35], which can accumulate up to concentrations of 10 μM to 5 mM both in vivo and in vitro [8,33].…”
Section: Introductionmentioning
confidence: 99%